MUI ISLAMIC COMMUNICATION STRATEGY IN SOCIALIZING HARAM FATWA HELPING BEGGERS IN MAKASSAR CITY - Firdaus Muhammad; Hartinah Sanusi; Khaerunnisa Khaerunnisa (International Conference on Social and Islamic Studies, 2021)
This research focused on the fatwa of the Indonesian Ulama Council (MUI) of South Sulawesi Province which prohibits making donations or helping beggars on the streets. The socialization of fatwas requires a process through Islamic communication strategies to be understood and applied by the people of Makassar City. The type of research is descriptive-qualitative with data collection methods through interviews, observations and documentation. The data research sources are the result of interviews of competent MUI scholars, local governments and street user communities, the fatwa documents of MUI and other related research articles. Research data analysis and conclusion using Miles and Huberman model qualitative data analysis techniques. This fatwa attracting variety of responses from community who refused and accepted. The people who refused this fatwa consider that religion commands them to give alms and do good to humans, especially the weak. Otherwise, people who received agreed that making donations on the streets had a more negative impact.  Furthermore, it also affects the increasing number of beggars and causes the weak of young generation. The fatwa affects the decreasing number of people who donated. This study showed that MUI's communication strategy through press conferences in public spaces by inviting several mass media has a better impact. The information about this fatwa become viral both in mainstream media, online and social media. More over, the Islamic communication strategy with the pattern of ‘qaul syadid’ makes the public confident with strong propositions and higher public expectations on MUI, so that the fatwa is effective. Another strategy is ‘qaul layyinan’, where MUI builds cooperation with local government to make laws as regulations to overcome the social impact of beggars on the street. The implication of this study is the emergence of a collective awareness of all elements of society not to donate or give anything to beggars to minimize the number of beggars through the empowerment of people to create more productive human resources.